A study on the building maintenance practices in students’ hostels at public universities - Nur Afifah Sanusi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Building maintenance practices in students’ hostels at the universities are very important to enhance students’ performance. The scope of the research is limited to three universities which are Universiti Malaya (UM), Universiti Putra Malaysia (UPM) and Universiti Teknologi MARA (UiTM). The findings of the research revealed corrective maintenance is the most practices of building maintenance that carried out in students’ hostels. From the findings, criteria of maintenance management such as “effective plan and policy of hostels maintenance management” and “method of maintenance management that undertaken is constantly reviewed” are the typical weaknesses. Moreover, criteria of employees’ expertise such as “employee is competent to perform building maintenance work” and “adequate training programmes to employees” are the common weaknesses occur in most universities. Lastly, criteria of materials such as “high quality and durable materials are used” and “materials are available and hardly out of stock” are the common weaknesses arise in the universities. For the improvement strategy of a better plan and policy of maintenance management in hostels, employees in organisation who handles the procedures must be competent. Supervisor has to handle the maintenance schedule to assure the method of maintenance management undertaken is constantly reviewed. Providing sufficient training to employees can enhance employees’ expertise. Supervisor has to be appointed to assure there are adequate training programmes to the employees. The improvement of the criteria of high quality and durable materials is materials need to follow the standards as specified. Supervisor should also monitor and ensure that the materials are always available.